DETEKSI PERUBAHAN PENGGUNAAN LAHAN DENGAN CITRA LANDSAT DAN SISTEM INFORMASI GEOGRAFIS: STUDI KASUS DI WILAYAH METROPOLITAN BANDUNG, INDONESIA - Nurrohman Wijaya (Geoplanning: Journal of Geomatics and Planning, 2015)
Land use change becomes one of the significant issues for planners and decision makers in urban and regional policy. Data, information, and tool sometimes turn to be a burden in the process of detection of land use change. It is expected that increasing of accessibility presently will be straightforward to conduct the land use change detection. This study aims to demonstrate the land use detection with data and tool that are available. Landsat images and Geographical Information System (GIS) analysis are used to detect land use change in the urban area of Bandung Metropolitan Area (BMA) in Indonesia in three periods, which are 1979, 2006, and 2014. Land use change of BMA is identified through satellite images of Landsat MSS 1979, Landsat TM 2006, and Landsat OLI 2014, and the use of GIS for analyzing the land use classification. Based on the results, expansion of urban area has been increasing. Development of settlement area is more growing, and forest land is significantly declining. The interesting result is the increasing of industrial and commercial areas. It indicates that most land use is changing from non-built up area to built up one, and urban area is sprawling to the surroundings. It gives a challenge for urban area development of BMA. Planners and policy makers take part in an important role to keep the urban area developing in a sustainability way.© 2015 GJGP UNDIP. All rights reserved.